2016
DOI: 10.1111/jeb.12959
|View full text |Cite
|
Sign up to set email alerts
|

Selection for distinct gene expression properties favours the evolution of mutational robustness in gene regulatory networks

Abstract: Mutational robustness is a genotype's tendency to keep a phenotypic trait with little and few changes in the face of mutations. Mutational robustness is both ubiquitous and evolutionarily important as it affects in different ways the probability that new phenotypic variation arises. Understanding the origins of robustness is specially relevant for systems of development that are phylogenetically widespread and that construct phenotypic traits with a strong impact on fitness. Gene regulatory networks are exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 129 publications
0
9
0
3
Order By: Relevance
“…5a, b and Supplementary Data 6 ). Previous theoretical work has suggested that stabilizing selection was important in promoting the evolution of network robustness 36 . Our result is one of the few 37 that provides empirical support for the role of stabilizing selection in evolving network robustness.…”
Section: Discussionmentioning
confidence: 99%
“…5a, b and Supplementary Data 6 ). Previous theoretical work has suggested that stabilizing selection was important in promoting the evolution of network robustness 36 . Our result is one of the few 37 that provides empirical support for the role of stabilizing selection in evolving network robustness.…”
Section: Discussionmentioning
confidence: 99%
“…Esta última propuesta fue verificada empíricamente a través del análisis genómico de la conservación de la red regulatoria del desarrollo floral en diferentes angiospermas (Dávila-Velderrain, Servin-Márquez y Álvarez-Buylla, 2013). También se han realizado contribuciones importantes sobre el papel de la plasticidad fenotípica (y la variabilidad no genética en general) en la adaptación y consistencia de sistemas biológicos en el contexto de la evolución de la modularidad de las plantas (Espinosa-Soto, 2016;Espinosa-Soto y Wagner, 2010;Espinosa-Soto et al, 2011a, b). Estos últimos estudios han generado predicciones interesantes sobre el papel que puede desempeñar la plasticidad de los genotipos en la evolución adaptativa (Espinosa-Soto et al, 2011a, b).…”
Section: Modelos Del Paisaje Epigenético: Un Marco Teórico Para La Eco-evo-devounclassified
“…También explora cómo emergen la plasticidad fenotípica (i.e., variación fenotípica de un mismo genotipo en distintos ambientes) y las normas de reacción de un genotipo (i.e., patrón de cambio fenotípico de un genotipo ante variaciones de un factor ambiental). Finalmente, se investiga cuál es el papel de la plasticidad en la evolución fenotípica adaptativa y no adaptativa (Espinosa-Soto, 2016;Espinosa-Soto, Martin y Wagner, 2011a, b).…”
Section: Introducción ¿Qué Es La Ecología Evolutiva Del Desarrollo?unclassified
See 1 more Smart Citation
“…This mechanism is crucial for evolutionary innovations, because genotypes which control gene-gene interactions can change profoundly without affecting phenotypes which represent gene activities or expression concentrations [2]. Wagner's GRN model motivates research on the evolution of genetic networks, and has been successfully employed to study many fundamental evolutionary and ecological questions [15,16,17,18,19,20,21,22,23,11,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52] (See [12] for an in-depth review).…”
Section: Introductionmentioning
confidence: 99%